2022
DOI: 10.1177/14034948221141516
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian adolescents’ use of energy drinks and painkillers and misuse of prescription drugs prior to and during the initial COVID-19 pandemic year: Evidence from the MyLife study

Abstract: Aims: This study aimed to examine and compare the use of energy drinks, over-the-counter (OTC) painkillers and misuse of prescription drugs in two cohorts of Norwegian adolescents entering high school (i.e. grade 11) immediately prior to and during the initial year of the COVID-19 pandemic. Methods: Accelerated longitudinal design and multi-cohort sampling enabled identification of the two socio-demographically comparable cohorts of grade 11 students: (a) COVID-19 cohort assessed in the autumn of 2020 ( n=915)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Some studies have demonstrated the relationship between COVID-19 and sleep, both longer sleep duration 40 and increased sleep problems. 41 Another study from Norway, though in adolescents, demonstrated a higher intake of ED during the COVID-19 pandemic compared with before, 42 consequently one could speculate whether the pandemic had an impact on the consumption rates of ED that we found in the current study.…”
Section: Discussionmentioning
confidence: 53%
“…Some studies have demonstrated the relationship between COVID-19 and sleep, both longer sleep duration 40 and increased sleep problems. 41 Another study from Norway, though in adolescents, demonstrated a higher intake of ED during the COVID-19 pandemic compared with before, 42 consequently one could speculate whether the pandemic had an impact on the consumption rates of ED that we found in the current study.…”
Section: Discussionmentioning
confidence: 53%